Los territorios metropolitanos como escenarios de operación de los dispositivos funcionales de la globalización. Caso de estudio: la Zona Franca del Pacífico (Palmira, Colombia) - Ramírez Moreno, Andrés Felipe; Martínez Toro, Pedro Martín; Paredes Mora, Diana Carolina (Revista de Geografía Norte Grande, 2025)
The phenomenon of globalization has been promoting a series of morphological and functional transformations in the main urban territories of the planet, which have acquired a strategic character for the world economy. In this context, the French sociologist François Ascher (1946-2009) proposed, in 1994, the concept of "metapolis", which seeks to analyze the multi-scale territorial logic promoted by globalization. This theoretical proposal emphasizes the processes of transnational articulation promoted by globalization through a series of devices that are located in certain metropolitan territories of the planet. In this sense, the objective of this article is to characterize the economic operations developed by the Pacific Free Trade Zone as a functional device of globalization that participates in the process of formation of the "planetary metapolis". For the development of this research, a mixed methodology is used, which contemplates the review of different bibliographic sources related to the subject, as well as the treatment of statistical data referring to the economic activities carried out by the free zone under study. It is concluded that the Pacific Free Trade Zone is a metapolitan device that allows the insertion of the national market into the economic circuits promoted by contemporary globalization.